Prevalence of Cognitive Impairment in Peritoneal Dialysis Patients and Associated Factors - Aleksandra Golenia; Norbert Zolek; Piotr Olejnik; Ewa Wojtaszek; Tomasz Glogowski; Jolanta Malyszko (Karger Publishers, 2023)
Background: Cognitive impairment (CI) in patients with chronic kidney disease, including those treated with renal replacement therapy, is a growing problem worldwide. Objectives: The study aimed to assess the prevalence of CI and associated factors in patients undergoing peritoneal dialysis (PD). Methods: In this cross-sectional study, 18 consecutive patients with PD therapy and 15 controls were evaluated for CI using the Addenbrooke's Cognitive Examination III (ACE III) test. Results: The prevalence of CI was 33% in patients and 27% in the control group and was not statistically significant. A higher prevalence of CI was found in subjects aged ≥65 years old than in those <65 years old (p = 0.02), but only in the control group. The prevalence of CI in PD patients over and under 65 years of age did not differ statistically significantly (p = 0.12). Memory and verbal fluency were the most affected cognitive domain in PD patients with CI (p = 0.00, p = 0.04, respectively). There was a significant correlation between higher educated PD patients and the ACE III test results. The duration of dialysis did not affect the results of the cognitive screening test. Conclusions: CI is a growing problem in the course of chronic kidney disease and dialysis therapy. It seems that cognitive problems may occur in patients undergoing PD at a younger age than in the general population with particularly affected memory and verbal fluency. Higher educated patients score better on the cognitive screening test.